2014
DOI: 10.1007/s11033-014-3576-9
|View full text |Cite
|
Sign up to set email alerts
|

Lily breeding by using molecular tools and transformation systems

Abstract: In our review, we highlighted the progresses made in molecular breeding of lily's flowering, including the ABCDE models, the gene cloning, the establishment of regeneration system, the gene transformation methods, the transgene technology application in lily. Meanwhile, questions that were met at present in molecular breeding in flowering of lily were underlined, and we provide viable solutions. Although many researches on lily literature had been published in the world, in our review, we provided a valuable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Lilium is difficult to transform genetically, and only a few Lilium transformations have been achieved thus far [8,9,10,11,12,13,47,48,49], which is largely due to a high rate of chimerism and low transformation efficiency. It has been reported that genetic transformation of Lilium is greatly affected by the genotype of the plant as well as the type and status of the receptor tissue used for Agrobacterium infection [50]. Because embryogenic callus is composed of a large number of embryogenic cells, and every single cell has the potential to develop into a somatic embryo, using embryogenic callus as a receptor material would in all probability reduce or even avoid chimerism.…”
Section: Discussionmentioning
confidence: 99%
“…Lilium is difficult to transform genetically, and only a few Lilium transformations have been achieved thus far [8,9,10,11,12,13,47,48,49], which is largely due to a high rate of chimerism and low transformation efficiency. It has been reported that genetic transformation of Lilium is greatly affected by the genotype of the plant as well as the type and status of the receptor tissue used for Agrobacterium infection [50]. Because embryogenic callus is composed of a large number of embryogenic cells, and every single cell has the potential to develop into a somatic embryo, using embryogenic callus as a receptor material would in all probability reduce or even avoid chimerism.…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding resistance to fungal and viral diseases have been found, including those resistant to Fusarium wilt in Asiatic hybrids [81] and L. regale [8285], leaf blight in L. regal [86, 87], and TBV and LMoV in Longiflorum [72, 88, 89], Asiatic hybrids [73] and L. regal [74]. These valuable genes have been/are being used for breeding of novel cultivars resistant to abiotic and biotic stresses in classic and biotechnological strategies in Lilium [13, 72, 7476, 85]. Cryopreservation of these valuable genes will certainly ensure supply genetic resources for breeding of novel lily cultivars in the future.…”
Section: Future Prospects and Conclusionmentioning
confidence: 99%
“…There are more than 300 new registrations of Lilium cultivars each year and approximately 9500 cultivars in total globally [11]. There is a demand for new, novel lily cultivars from the production industry [4, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lily species and hybrids (genus Lilium in the botanical family Liliaceae) are widely used as cut flowers, and are also planted in parks, courtyards, and home gardens. It has always been the goal of lily breeding to produce lilies with colorful flowers ( Liu et al, 2014 ). Moreover, petals are the important part of many ornamental plants, and the different colors, tones, and intensities of the petals are always due to the presence and contents of various anthocyanin pigments, which directly affects the ornamental value of plants ( Alappat and Alappat, 2020 ).…”
Section: Introductionmentioning
confidence: 99%